Frequency of brain injury in a forensic psychiatric population - Souza,Carlos Alberto Crespo de (2003)
OBJECTIVE: Over the last years, a growing number of studies involving individual patients and/or populations have demonstrated that Traumatic Brain Injuries (TBI) determine innumerable psychiatric symptoms, including significant alterations which may influence diagnoses, prognosis and treatment, not to mention clear psychosocial implications (both legal and those related to social security). The objectives of this study were 1) to detect the existence of TBI in a forensic psychiatric population before the occurrence of the wrongs; 2) To verify whether or not those injuries had been identified by the experts at the psychiatric institution. METHOD: 3,323 records of patients examined by forensic experts at the Forensic Psychiatric Institute Dr. Maurício Cardoso in Porto Alegre were analyzed; the records covered the period between 1995 and 1999. RESULTS: in the studied population, there were 133 cases of TBI prior to the wrongs, 39 of which were mild, and 94, moderate or severe. Out of the total number of TBI cases found, 111 cases were not taken into account, many of them having motoric, cognitive, psychic and sensori perception alterations. CONCLUSION: the significant number of patients that had had TBI before having committed a wrong - a fact that had not been considered by the experts (neurologists and psychiatrists) at the institution - is a strong indicator of how little attention is paid to the consequences of these injuries. Considering the relevance of the psychosocial aspects, new studies should be conducted in psychiatric populations to increase the knowledge about the consequences of these injuries.